Stimulated effect of SMBI on low-to-high confinement transition of tokamak plasmas. (21st July 2020) - Zhong, W.L.; Zou, X.L.; Liang, A.S.; Feng, B.B.; Xiao, G.L.; Chen, C.Y.; Shi, Z.B.; Xiao, W.W.; Yang, Z.C.; Shi, P.W.; Wang, Z.X.; Jiang, M.; et al.
Abstract: The impact of supersonic molecular beam injection (SMBI) fuelling on the plasma turbulence and shear flows, which form a self-consistent state, has been studied in the HL-2A tokamak. The SMBI flattens the shear layer by the collisional flow damping and increases the turbulence intensity. It is found that the SMBI can enhance the non-linear regulation dynamics and acts as an external tool for turbulence quench via stimulating two dynamic processes. The SMBI-stimulated non-linear interactions facilitate the L-H transition at the marginal heating power for accessing the H-mode. The effective reduction of the H-mode power threshold by SMBI is demonstrated. The result suggests that the SMBI could be a general tool for realization of controllable L-H transition via reducing the H-mode power threshold in future devices.